2021
DOI: 10.1016/j.coelec.2021.100688
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of nanostructured catalysts for electrochemical energy conversion: Current trends and innovative strategies

Abstract: This review discusses the latest advances in electrodeposition of nanostructured catalysts for electrochemical energy conversion: fuel cells, water splitting and carbon dioxide electroreduction. The method excels at preparing efficient and durable nanostructured materials, such as nanoparticles, single atom clusters, hierarchical bifunctional combinations of hydroxides, selenides, phosphides, etc. Yet, in most cases, chemical composition cannot be decoupled from catalyst morphology. This compromises the ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 79 publications
(182 reference statements)
0
15
0
Order By: Relevance
“…The ITO is further decorated with hemispherical Ni or Pt NPs grown by electrodeposition. Electrodeposition offers several advantages compared to chemical synthesis: in addition to guaranteeing a good electrical contact between the NPs and the substrate, [34] it can produce NPs with a wide range of sizes, allowing for the screening of size‐dependent electrochemistry at the single NP level [35, 36] . Moreover, optical microscopy allows an in situ monitoring of the NPs’ growth [37–39] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ITO is further decorated with hemispherical Ni or Pt NPs grown by electrodeposition. Electrodeposition offers several advantages compared to chemical synthesis: in addition to guaranteeing a good electrical contact between the NPs and the substrate, [34] it can produce NPs with a wide range of sizes, allowing for the screening of size‐dependent electrochemistry at the single NP level [35, 36] . Moreover, optical microscopy allows an in situ monitoring of the NPs’ growth [37–39] …”
Section: Resultsmentioning
confidence: 99%
“…Electrodeposition offers several advantages compared to chemical synthesis: in addition to guaranteeing a good electrical contact between the NPs and the substrate, [34] it can produce NPs with a wide range of sizes, allowing for the screening of size-dependent electrochemistry at the single NP level. [35,36] Moreover, optical microscopy allows an in situ monitoring of the NPs' growth. [37][38][39] The surface confined by a miniaturized electrochemical cell containing a Ni 2 + solution is subjected to HER by applying a negative potential bias cycle in a cyclic voltammetry (CV) experiment (Figure 1c) while optical images of the surface are continuously acquired under optical microscopy observation in a reflection mode at 20 Hz by a CMOS camera.…”
Section: Resultsmentioning
confidence: 99%
“…The production of nanostructured electrocatalysts for EES devices using electrodeposition is receiving immense interest. Important benefits of the approach include conformality, precision current/voltage control of the deposition, and a solid link between the electrocatalyst and substrate that increases durability and performance 21 . The idea behind this method is to reduce dissolved metal cations using an electric current in order to electrode coating with a uniform layer of metal.…”
Section: Synthesis Strategiesmentioning
confidence: 99%
“…However, this method is limited to a few targets because the electrodeposition requires conducting materials as a substrate to transport electrons for the reduction of ions. Hence, studies about the application of electrodeposited films have been mainly reported for photovoltaic [39][40][41][42] or electrocatalytic [43,44] devices, which benefit from metal chalcogenides deposited on conducting materials. In contrast, the application of metal chalcogenides synthesized by electrodeposition has been rarely studied for electric devices, sensors, and photodetectors, which have been widely researched by vacuum-based thin film fabrication methods.…”
Section: Doi: 101002/admi202202023mentioning
confidence: 99%